School Principals' Strategies for Improving the Professional Competence of Teachers - Setiawan, Adrianus Danang; Widayatsih, Tri; Pahlawan, Pahlawan (research, training and philanthropy institution Natural Aceh, 2024)
This research aims to determine the strategies, obstacles, and solutions carried out by the Principal of SD Negeri 07 Sembawa to improve teachers' professional competence. This research is fundamental because, based on the initial observations, two main problems were found: the quality of learning and the need for more technology and communication in learning activities. This research uses descriptive qualitative research methods, with five sources: the school principal, three teachers, and one student. Based on data obtained in the field from observation, interviews, and documentation, the research results show that the strategy implemented by the Principal of SD Negeri 07 Sembawa to increase teacher competency, namely by carrying out routine supervision once a semester, including and involving teachers to be active in seminars and training activities to improve the quality of learning and use of ICT. The obstacles faced by the Principal of SD Negeri 07 Sembawa are insufficient adequate facilities and infrastructure, lack of teacher motivation, and the majority of teachers entering retirement. The solution taken by the Principal of SD Negeri 07 to overcome these obstacles is by taking an individual approach, facilitating teachers to be active in self-development activities, and evaluating teacher performance with supervision activities.